The Effectiveness of the Problem-Based Learning Model Assisted by Augmented Reality on Learning Outcomes in the Science Subject of Light and Its Properties for Class V - Sagita Ayuk Lestari; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2025)
The use of learning models and media that do not comply with the process standards in Permendikbudristek Number 16 of 2022 has an impact on low student learning outcomes. This study examines the effectiveness of the AR-assisted PBL Model on the learning outcomes of Class V Science at Gugus Mawar Elementary School, Semarang City compared to the teacher-assisted PBL Model assisted by PPT. This study is included in the type of experimental research with a quasi-experimental research design in the form of Nonequivalent Control Group Design. The population in this study were 77 class V students of Gugus Mawar Elementary School using the purposive sampling technique. In this study, SDN Kemijen 02 acted as the experimental class and SDN Kemijen 01 as the control class. The results of the t-test obtained a sig value of 0.000, which is less than 0.05 so that Ho is rejected and Ha is accepted. This is supported by the results of the N-Gain test for the experimental class of 0.58 and the control class of 0.50. So it can be concluded that the AR-assisted PBL Model is more effective than the PPT-assisted teacher version of the PBL Model on the learning outcomes of class V of Gugus Mawar Elementary School.